Geology of the Ilímaussaq alkaline intrusion, South Greenland. Description of map and structure - Ferguson, J. (Meddelelser om Grønland, 1964)
The Ilímaussaq Intrusion forms part of the alkaline province of South Greenland. It is thought that all the alkaline intrusions in South Greenland were emplaced in the basement rocks towards the close of the Gardar period. Rb/Sr age determinations of the Kûngnât and Ilímaussaq rocks give values of 124.0 m.y. and 1086 m.y. respectively. The Ilímaussaq Intrusion intruded into the Julianehåb granite and the overlying sandstones, basalts and trachytes of the Gardar continental series. The trachytes probably represent an extrusive phase of the Ilímaussaq igneous activity. E.S.E. faulting, initiated in Ketilidian or early Kuanitic time, continued through the Sanerutian into the Gardar period and is thought to be the controlling factor of emplacement for the major alkaline centres. The earliest magma of the Ilímaussaq Intrusion had an augite syenitic composition. After emplacement this magma proceeded along an undersaturated differentiation trend. The in situ undersaturated differentiation was interrupted by an injection of alkali granite into the upper parts of the intrusion. Following this, in situ undersaturated differentiation was resumed, and, aided by volatiles, formed a magma of peralkaline composition (agpaitic). Crystallization took place from the roof downwards with simultaneous gravity accumulation on the floor of the intrusion. Finally a residual liquid, rich in volatiles, was trapped between the downward crystallizing naujaite and the gravity accumulating kakortokites. As a result of faulting and/or slumping, the residual crystal mush was injected into the overlying brecciated rocks where it crystallized to form the fissile lujavrites. Minor syenitic intrusions in the complex probably mark the last phase of igneous activity.